Motivations and use of video games in engineering students - Rosa Núñez-Pacheco; Osbaldo Turpo-Gebera; Aymé Barreda-Parra; Elizabeth Vidal; Eveling Castro-Gutierrez; Ignacio Aguaded (OmniaScience, 2023)
The use of video games has increased exponentially worldwide, mainly among the youth population. The main objective of this article is to evaluate the consumption habits and motivations of engineering students to play video games. To this end, an instrument to measure the use of video games and a scale of motivations were administered to 633 students enrolled in different academic engineering programs at a Peruvian public university. It was found that 91.3% of students play video games, compared to 8.7% who have never played them; it was also found that their use is greater among male students (95%) than among female students (73.4%). Likewise, it was found that these students prefer strategy video games, and that they mostly play them for escape and entertainment, and for socioemotional activation. It is concluded that consumption habits and motivations are related, since the greater the consumption of video games, the greater the motivation is for young people to play them.